Teaching in China: An Experience of Academic Journey Beyond Borders - Mohamad Rusydi, Mohamad Yasin; Abdul Nasir, Abd Ghafar; Azim, Arshad (UMPSA, 2025)
Earlier this year, we had the privilege of spending two weeks at Sichuan Aerospace Vocational College (SCAVC) in Chengdu, China. This visit was part of a meaningful collaboration between Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and SCAVC through an academic programme by UMPSA Advanced.